Key Indicators in Analyzing the Sustainability of Afghanistan's Natural Resources - Yar, Fayaz Gul Mazloum; Sail, Izat Ullah; Zahid, Shamsurahman (Formosa Journal of Multidisciplinary Research, 2024)
The research investigates the factors influencing the sustainability of Afghanistan's natural resources, aiming to guide the country towards sustainable development and poverty alleviation. Utilizing the Analytic Hierarchy Process (AHP) and strategic planning models, the study identifies and prioritizes key factors such as organizational structure and management, and economic, social, cultural, and ecological aspects. The findings reveal that organizational and managerial structure is the most critical factor, with a weight of 38%. The research emphasizes the necessity of integrated and systematic management of natural resources, which could improve economic and social well-being. It also highlights the importance of strategic planning, monitoring, and evaluation to ensure effective resource management. The study proposes a model for sustainable natural resource management that includes community empowerment, knowledge integration, economic viability, and enhanced communication among stakeholders. The research concludes that a comprehensive understanding of all influencing factors and their interactions is essential for designing a model for sustainable natural resource management.